Development of porous ceramics for gas burners - C. Pinho (2008)
The present work aims to develop porous ceramic plates based on cordierite, using the polymer foam replication method, to be used for gas burners. Ceramic foams were produced by coating polyurethane foams of different pore sizes with ceramic powders dispersed in aqueous slurries. The final porous structures were shown to depend on the structure of the original polymer sponge and on the details of the fabrication procedure. However, a suitable process control enabled to obtain a close relation between the final properties and the template polymer characteristics. The performance of the porous cordierite plates, with different pore size distributions, as medium burners was tested and compared by measuring the pressure drop in the burner against the air flow rate. It could be concluded that good performance is achieved with the higher porous materials due to its higher porosity fraction, and more suitable pore size range.